1999
DOI: 10.1046/j.1365-3156.1999.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epidemiology of host predisposition microfilaraemia in human loiasis

Abstract: SummaryEvidence is accumulating from experimental and human studies that genetic factors are involved both in the control of infectious diseases and in the regulation of infection levels and clinical presentation. So far few studies have investigated the role of these genetic factors in human infection by the filarial parasite Loa loa. We present a segregation analysis on 74 nuclear families who live in the tropical rainforest of southern Cameroun and are exposed to homogeneous loiasis transmission. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 30 publications
1
25
0
1
Order By: Relevance
“…45 It has been shown that host genetic factors, probably associated with specific immunologic responses against the Loa microfilariae, predispose a person to become microfilaremic or amicrofilaremic. 46 Such factors might explain rare occurrence of splenic involvement in loiasis in humans. As stated by Fain, histologic examinations of spleen tissue in persons infected with L. loa would shed light on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…45 It has been shown that host genetic factors, probably associated with specific immunologic responses against the Loa microfilariae, predispose a person to become microfilaremic or amicrofilaremic. 46 Such factors might explain rare occurrence of splenic involvement in loiasis in humans. As stated by Fain, histologic examinations of spleen tissue in persons infected with L. loa would shed light on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, during preliminary analyses, the NBD model, when fitted to the complete observed distributions of mf densities (including zero densities), did not provide satisfactory fits, whereas the zero-truncated NBD model provided adequate fits. Thus, assuming that the zero count class may not be reliable because only y60 % of the infected population would be genetically predisposed to present with microfilaraemia (Garcia et al 1999), and that some individuals may be false-negatives (due to the lack of sensitivity of the blood film method when microfilaraemia is low), we chose the zero-truncated NBD (tNBD) model (Pichon et al 1980 ;Grenfell et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that there could be genetic predisposition to microfilaremia and that predisposed subjects might be genetically unable to mount an efficient immune response against Loa loa antigens. 43,44 Genetic studies in severe clinical malaria using segregation analysis and linkage analysis for candidate chromosomal regions have identified specific loci in the human response to malarial infection. [45][46][47] In our study, we have identified two candidate genes, which could influence susceptibility to filarial infection.…”
Section: Discussionmentioning
confidence: 99%